2020
DOI: 10.1002/fsh.10390
|View full text |Cite
|
Sign up to set email alerts
|

Reaching Underserved Populations through a Fisheries Education Program

Abstract: Environmentally literate citizens capable of making informed decisions are essential to successfully managed fisheries. Fisheries‐focused environmental education programs may help build environmental literacy, but experimental evaluations are needed to determine the effectiveness of fisheries education programs. We begin addressing this need with a study of “Shad in the Classroom.” The program engages students in American Shad Alosa sapidissima restoration through rearing and releasing fry. We used a pre/post,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Key findings across these studies are that EE programming typically benefits those with non-dominant identities as well as, or to a greater degree than, those with dominant identities, leveling the playing field by differentially helping groups who typically fall behind (i.e., producing equigenic impacts: Kuo et al, 2019). For instance, findings from Szczytko et al (2020) showed that race was not a factor in young people's connection to nature, despite previous assumptions to the contrary, and Clark et al (2020) found that EE programs centering on fisheries had positive impacts on all learners, not just a certain group. Additionally, multiple studies have reported that EE programming has positive impacts particularly for girls (Stevenson et al, 2021) and children with learning disabilities (Szczytko et al, 2018).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Key findings across these studies are that EE programming typically benefits those with non-dominant identities as well as, or to a greater degree than, those with dominant identities, leveling the playing field by differentially helping groups who typically fall behind (i.e., producing equigenic impacts: Kuo et al, 2019). For instance, findings from Szczytko et al (2020) showed that race was not a factor in young people's connection to nature, despite previous assumptions to the contrary, and Clark et al (2020) found that EE programs centering on fisheries had positive impacts on all learners, not just a certain group. Additionally, multiple studies have reported that EE programming has positive impacts particularly for girls (Stevenson et al, 2021) and children with learning disabilities (Szczytko et al, 2018).…”
Section: Introductionmentioning
confidence: 94%
“…A first step at understanding how to foster such a sense of belonging is to better understand how learners from diverse identities may uniquely engage with EE programming. Relevant EE studies focused on specific identities have examined how factors such as race and ethnicity (Larson et al, 2011;Stevenson et al, 2013;Clark et al, 2020;Szczytko et al, 2020), gender (Stevenson et al, 2021), and learning differences (Szczytko et al, 2018), may shape how various learners benefit from EE opportunities. Key findings across these studies are that EE programming typically benefits those with non-dominant identities as well as, or to a greater degree than, those with dominant identities, leveling the playing field by differentially helping groups who typically fall behind (i.e., producing equigenic impacts: Kuo et al, 2019).…”
Section: Introductionmentioning
confidence: 99%